SULTAN HASANUDDIN'S COMIC BOOK AS A MEDIA FOR DELIVERING INDONESIAN HISTORY - Kurniawan, Sulistyo Agung Dwi; Syafii, Syafii; Budi Utomo, Kamsidjo (Arty: Jurnal Seni Rupa, 2022)
This study project was motivated by the decreasing interest in reading among adolescents, especially reading books on history, the decreasing reading rate resulting in less information absorption so that they forgot the importance of studying history. Because of this problem, the writer has the idea to bring back the big story that has happened in Indonesian history with a more modern look with the title "Sultan Hasanuddin" so that it attracts readers to learn the importance of history. The purpose of this study project is to produce a comic book about the heroism of Sultan Hasanuddin as a means of conveying Indonesian history in an effort to increase youth reading interest with local stories. This study project is expected to provide insight into the picture of Indonesia in the past that the author conveyed which is packaged into a comic book of Sultan Hasanuddin, which has an interesting visualization of images for teenagers. That way Indonesian teenagers are able to absorb the essence of what the author says by not never giving up in order to achieve their goals, not easily breaking up in the face of obstacles that get in the way. It is hoped that this comic can be used as a comic book that will be published later.